(untitled) (Sains Humanika, 2016)
It is important in the teaching of Islamic Education to be infused with thinking skills so that students can inteprate Islamic teaching into their life context. Nevertheless, the implementation of it in the teaching of Islamic Education is seen as lacking in stimulating the students’ thinking ability. It is crucial to ensure the Islamic Education teachers (IET) to develop their critical thinking attributes first before they implement it on their students. To develop this attribute among the teachers, it will not be easy since they have to allocate more time, more energy and a lot of systematic and continuous collaborations with other parties. Therefore, it is very important to highlight this issue. This study used content analysis methodology of previous research related to the development factors of IET as a critical thinker. This study found that there are two main factors including internal and external factors. These two factors are discussed based on the Ibn Khaldun Educational Theory and Dunkin & Biddle Teaching and Learning Model. Hopefully this article contributes to the development of critical thinking quality among the Islamic Education teachers on their own individual effort or in the higher level towards the effective teaching of Islamic Education.